Metallothionein 2A with Antioxidant and Antitumor Activity Is Upregulated by Caffeic Acid Phenethyl Ester in Human Bladder Carcinoma Cells - Hsin-Ching Sung; Kang-Shuo Chang; Syue-Ting Chen; Shu-Yuan Hsu; Yu-Hsiang Lin; Chen-Pang Hou; Tsui-Hsia Feng; Ke-Hung Tsui; Horng-Heng Juang (MDPI AG, 2022)
Functions of metallothionein 2A (MT2A) in bladder cancer have not been extensively explored even though metallothioneins are regarded as modulators in several biological regulations including oxidation and cancerous development. We evaluated MT2A in bladder carcinoma cells in terms of the mechanisms of regulation and the underlying functions. MT2A overexpression not only downregulated endogenous ROS but also blocked ROS induced by H2O2. We used the annexin V-FITC apoptosis assay to determine the modulation of H2O2-induced cell apoptosis by MT2A expression. Results of immunoblot and reporter assays indicated that caffeic acid phenethyl ester (CAPE) treatment induced MT2A and heme oxygenase-1 (HO-1) expressions; moreover, the involvement of CAPE in either upregulation of the HO-1 expression or downregulation of endogenous ROS is MT2A dependent in bladder carcinoma cells. Knockdown of MT2A increased invasion and cell growth in vitro and in vivo, whereas ectopic overexpression of MT2A had the reverse effect in bladder carcinoma cells. Unlike bladder cancer tissues, the real-time reverse transcriptase-polymerase chain reaction (RT-qPCR) analysis showed a significant level of MT2A mRNA in the normal bladder tissues. Collectively, our results indicated that MT2A is acting as an antioxidant and also a tumor suppressor in human bladder carcinoma cells.